1976
DOI: 10.1111/j.1365-2133.1976.tb00820.x
|View full text |Cite
|
Sign up to set email alerts
|

HL-A antigens in patients with guttate psoriasis

Abstract: Tissue typing was performed on lymphocytes of sixty-two patients with guttate psoriasis, in forty-four of whom this was the first manifestations of the disease. In 84% of cases, the guttate psoriasis was preceded by a clinical infection. A highly significant excess of antigen W17 (HLA-BW17) was found in patients when compared with healthy population. In common with some other studies antigens HL-A13 (HLA-B13), W15 (HLA-BW15) and W21 (HLA-BW21) were found in excess but these became non-significant after correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 15 publications
0
29
0
1
Order By: Relevance
“…Another disease manifestation is guttate psoriasis that presents itself as sudden dissemination of small, red, and scaly papules. Guttate psoriasis is frequently identified as the first manifestation of the disease in younger individuals and is reported to develop into chronic plaque psoriasis in a large proportion of patients (Williams et al, 1976). Flares of guttate psoriasis can also occur in individuals with chronic plaque psoriasis.…”
mentioning
confidence: 99%
“…Another disease manifestation is guttate psoriasis that presents itself as sudden dissemination of small, red, and scaly papules. Guttate psoriasis is frequently identified as the first manifestation of the disease in younger individuals and is reported to develop into chronic plaque psoriasis in a large proportion of patients (Williams et al, 1976). Flares of guttate psoriasis can also occur in individuals with chronic plaque psoriasis.…”
mentioning
confidence: 99%
“…The predominant phenotype, however, may change into other types in the course of disease. For example, chronic plaque psoriasis may transform into inflamed guttate lesions; conversely, guttate psoriasis develops into plaque psoriasis in approximately 70% of patients8. The mechanism underlying this change in psoriatic phenotype is not clearly understood, but it may be related to a hyperactive immune pathology associated with intercurrent infections, differences in susceptibility or disease-modifying genes5.…”
Section: Introductionmentioning
confidence: 99%
“…Associations between HLA anti gens and infection-related exacerbation [Karvonen, 1975], streptococci-related guttate psoriasis [Schoejim'M.vetal., 1974;Williams et al, 1976] and the humoral immune response to streptococcal antigens [Bertrams et al, 1974] have also been reported in psoriasis.…”
Section: Introductionmentioning
confidence: 99%